Poultry farmers' utilization of information in Lagelu Local Government Area, Oyo State of Nigeria (2006)
This study investigated poultry farmers' access and utilization of extension information in Lagelu Local Government Area of Oyo State. Data were collected using structured questionnaire. The results indicate that poultry farmers obtain information from a variety of sources with television been the most prominent (68%). Animal health it was found is the top information need of poultry farmers (52%). Severe constraints to poultry production are cost of obtaining information (64%), veterinary services (66%) and non availability of extension agents (63%). The study further shows that poultry farmers' sex and educational level are significantly related to sources of information. Similarly, poultry farmers' sex and educational level are related to their utilization of information. Non availability of extension agents, cost of inputs are also significantly related to farmers' utilization of information. The results imply that paucity of extension workers and increased cost of inputs reduce the probability of farmers utilizing available technologies or information.